Analysis of the Relationships Between Selected Budget Items of Communes in the Agglomeration of Szczecin and the Demographic Manifestations of the Phenomenon of Suburbanisation of Szczecin in the Years 2002–2010 - Gnat, Sebastian (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Suburbanisation is understood as "urban functions spilling out of the city centres into the surrounding areas." It is a process that occurs universally, observed both in developed and developing countries. Essentially, it happens in large urban centres and is seen as one of the phases of their development. The article presents research on the demographic and in part the financial aspect of this phenomenon for communes surrounding the largest city in Western Pomerania – Szczecin. It is said that for the neighbouring communes, suburbanisation is a positive phenomenon that allows the communes to obtain additional income. However, the increasing interest in areas intended for single-family housing is also linked to expenditure especially investment in the technical infrastructure. The article will present a study of the relationship between the proposed rate of suburbanisation and selected items in the budgets of the communes of Kołbaskowo, Dobra (Szczecińska), Police, Goleniów, Kobylanka, Gryfino and Stare Czarnowo. The period of analysis covers the years 2002–2010. Relationship analysis will provide answer to question: is greater influx of people into the studied communes related to the size of chosen expenditures.